Ilusi Kedamaian: Analisis Multidisiplin tentang Ideologi dan Dinamika Konflik Madara Uchiha dalam Naruto - Ahmad Rosikhul Fahmi; M. Luthfi Luqman Al Mustofa (Universitas Diponegoro, 2025)
Madara Uchiha, the principal antagonist in Masashi Kishimoto’s Naruto series, embodies the paradox of seeking peace through authoritarian control. His character integrates psychological trauma, political philosophy, and narrative symbolism, reflecting real-world tensions between idealism and power. This study analyzes Madara’s internal-external conflicts, philosophy of peace, and narrative impact through an interdisciplinary lens (psychoanalytic, Marxist, and Machiavellian theories). Qualitative critical-scene analysis of manga volumes 55–72 (Naruto), focusing on 26 purposively sampled scenes (Vol. 65–67) depicting Madara’s trauma, ideology, and pivotal conflicts. Madara’s trauma (e.g., loss of his brother Izuna) fuels a pathological id-superego conflict, distorting his initial idealism into a Nietzschean will to power and Machiavellian realism. His